Antimicrobial Evaluation of Sequentially extracted Leaf of Vernonia auriculifera Hiern (Rejicho) - Teshale Etiso Wado; Sultan Suleman; Tesfaye Mohammed (BMC, 2022)
Abstract Background Though there are reports about V. auriculifera antimicrobial activity, there is not enough information about its activity on some bacterial and fungal species. Besides, there was no quantitative evaluation done for phytochemicals previously. Therefore, the main purpose of this research work is to evaluate the antimicrobial activity and quantitative evaluation of the phenol and flavonoid contents of V. auriculifera. Objectives The objective of this study was to conduct the antimicrobial and quantitative evaluation of a sequentially extracted leaf of Vernonia auriculifera Hiern. Methods The leaves of the plant were cleaned with tap water and air-dried. The grounded leaf product was subsequently extracted by hexane, chloroform, and methanol in maceration flasks. Then the total phenol and total flavonoid content in each extract were determined. Standard strains of bacterial and fungal species were used to assess the antibacterial, and antifungal susceptibility test and to determine the minimum inhibitory concentration of crude extract. Result Extraction yield for hexane, chloroform, and methanol was 0.6 ± 0.05%, 1.7 ± 0.02%, and 3.3 ± 0.01% respectively. The total phenolic content of methanol extract was 72.998 ± 0.002 mg GAE /g. The total flavonoid content of hexane and chloroform extracts were 2.59 ± 0.004 mg QE/g and 9.6 ± 0.02 mg QE/g respectively. The antimicrobial activity test showed the chloroform extract was the most active against all test microorganisms. Conclusion This study has shown the activity of V. auriculifera against selected microorganisms of study. The chloroform extract was the most active as compared to the hexane and methanol extracts.